The challenges and opportunities for ethics in generative artificial intelligence in the digital age - Gabriel Silva-Atencio (Dyna)
Generative Artificial Intelligence (GenAI) emerged as a prominent tool in early 2023, renowned for its capability to generate unique texts and images from minimal input. Despite its growing popularity, the ethical implications of this technology remain under-explored. This study aimed to examine the ethical dimensions of GenAI, particularly focusing on the guidelines necessary during the lifecycle of the algorithms that drive it. We employed a qualitative, non-experimental, descriptive, and exploratory methodology. A comprehensive bibliometric analysis encompassed one hundred and fifty bibliographic references. The analysis highlighted significant concerns regarding algorithmic discrimination, justice, data privacy, and the inherent risks associated with this nascent technology. The findings reveal a pressing need for robust protocols to govern the development of GenAI applications to mitigate risks such as algorithmic bias and privacy breaches. Without such frameworks, the broader social and economic impacts of GenAI pose substantial challenges. This paper concludes by discussing the profound ethical implications of digital platforms driven by Generative Artificial Intelligence.